Vozes negras: a estética da diáspora no canto e na performance de cantoras negras brasileiras - Cruz, Luciana de Oliveira Miranda da (2021)
Introduction: situations such as racism, discrimination in professional performance, underprivileged economic condition and difficulties with the choice of the musical genre were portrayed in several biographies of black singers. Based on the deepening of ethnic-racial discussions, as well as an approximation with the aesthetics of the diaspora, will it be possible to envision an expansion in the performance of black singers in the current music scene in Brazil? Objective: Analyze how black singers of the current Brazilian music scene articulate its singing and performance from the perspective of the African Diaspora aesthetic. Method: Online interviews were conducted with the singers Ellen Oléria, Luedji Luna, Preta Rara and Xênia França, who have stood out in the recent music scene. The interviews followed a script with questions related to their career, singing, performance, aesthetics and the insertion of the black singer in the current music scene. Singers selected a video, which was consider the best representative of their work, and each one was analyzed and incorporated into the discussion. Results: Each of the four singers are close in age, around 35 years old, but they have different backgrounds and different career paths. The musical genres highlighted on their works were: Brazilian music, world music and rap. The musical influences named diverse between artists of Brazilian music and American black music, on the following genres: samba, jazz, soul and pop. In relation to vocal and body preparation, vocal techniques were pointed out, such as speech level sing, speech therapy, eutonia and yoga. On black image and aesthetics, were reported influences from candomblé, from the Afro-Futurist movement, certain inspirations based on intuition and on clothes that aim to deconstruct patterns. In performance, the construction takes place in the relation with the audience, in the connection with the music and through intuitive movement. The black voice, according to the singers, might be understood based on influences from the environment, characteristics such as strong and powerful voice, and aesthetic, emotional and socio-cultural issues. The four singers consider themselves black singers with more space in the current scenario, but note that visibility does not yet represent the size of the black population in Brazil. Final considerations: the above-mentioned singers, on their interviews, confirmed an increase in the visibility of black singers in the current music scene, probably due to a growth in the virtual world and black media. All of them bring elements in song and performance that put them in dialogue with the aesthetics of the African Diaspora, which impacts on the construction of new narratives and, consequently, on a greater strength in their artistic expressions